Selectively targeting disease‐restricted secretogranin III to alleviate choroidal neovascularization. Issue 1 (17th December 2021) - Ji, Liyang; Waduge, Prabuddha; Hao, Lili; Kaur, Avinash; Wan, Wencui; Wu, Yan; Tian, Hong; Zhang, Jinsong; Webster, Keith A.; Li, Wei
Abstract: Choroidal neovascularization (CNV), a leading cause of blindness in the elderly, is routinely treated with vascular endothelial growth factor (VEGF) inhibitors that have limited efficacy and potentially adverse side effects. An unmet clinical need is to develop novel therapies against other angiogenic factors for alternative or combination treatment to improve efficacy and safety. We recently described secretogranin III (Scg3) as a disease‐selective angiogenic factor, causally linked to diabetic retinopathy and acting independently of the VEGF pathway. An important question is whether such a disease‐selective Scg3 pathway contributes to other states of pathological angiogenesis beyond diabetic retinopathy. By applying a novel in vivo endothelial ligand binding assay, we found that the binding of Scg3 to CNV vessels in live mice was markedly increased over background binding to healthy choriocapillaris and blocked by an Scg3‐neutralizing antibody, whereas VEGF showed no such differential binding. Intravitreal injection of anti‐Scg3 humanized antibody Fab (hFab) inhibited Matrigel‐induced CNV with similar efficacy to the anti‐VEGF drug aflibercept. Importantly, a combination of anti‐Scg3 hFab and aflibercept synergistically alleviated CNV. Homozygous deletion of the Scg3 gene markedly reduced CNV severity and abolished the therapeutic activity of anti‐Scg3 hFab, but not aflibercept, suggesting a role for Scg3 in VEGF‐independent CNV pathogenesis and therapy. Our work demonstrates the stringent disease selectivity of Scg3 binding and positions anti‐Scg3 hFab as a next‐generation disease‐targeted anti‐angiogenic therapy for CNV.